Volume change rate before and after neoadjuvant systemic therapy of breast cancer is an efficacious evaluation index to predict pathological complete response - Xu, Yinggang; Zhang, Weiwei; Wang, Siqi; Xu, Lu; Xu, Haiping; Chen, Rui; Shi, Xiaoqing; Huang, Xiaofeng; Wang, Ye; He, Jinzhi; Shi, Wenjie; Wan, Xinyu; et al. (Frontiers in Oncology, 2023)
Neoadjuvant systemic therapy (NST) is widely applied in breast cancer treatment, but individuals respond differently to the same NST regimen. It is unclear which patients should adjust their NST regimen and what such an adjustment should be, especially for patients with radiologically partial response (PR). This study aimed to identify a quantitative efficacy evaluation index to evaluate the therapeutic effect of NST. 164 patients were enrolled in this study received four cycles of epirubicin and cyclophosphamide (EC), followed by four cycles of taxanes with trastuzumab [T(H)], if needed. Of patients with a volume change rate of EC treatment (δV1) below 0.80, more than half benefited from subsequent T(H) treatment compared with EC treatment. Importantly, for δV1 of 0.80 and higher, patients' subsequent T(H) treatment was not as efficient as previous EC treatment and they have a lower pathological complete response (pCR) rate. Across all patients, nanoparticle albumin-bound paclitaxel had a numerically higher pCR rate over other taxanes in patients with triple-negative breast cancer. This study showed that the volume change rate is better than the diameter change rate in monitoring the therapeutic effect of NST. Furthermore, δV1 is a good quantitative efficacy evaluation index to distinguish patients resistant to EC treatment and predict the pCR rate and guide the adjustment of individualized NST regimens.